Crystal structure and Hirshfeld surface analysis of 1-benzyl-3-(prop-2-yn-1-yl)-2,3-dihydro-1H-1,3-benzodiazol-2-one - Saber, Asmaa (Acta Crystallogr E Crystallogr Commun, 2018)
The title compound, C(17)H(14)N(2)O, is built up from the planar benzodiazole unit linked to the benzyl and propynyl substituents. The substituents are rotated significantly out of the benzodiazole plane, where the benzyl group is inclined by 68.91 (7)° to the benzodiazole unit. In the crystal, the molecules are linked via intermolecular C—H(Bnzdzl)⋯O and C—H(Bnzy)⋯O (Bnzdzl = benzodiazole and Bnzy = benzyl) hydrogen bonds, enclosing R (4) (4)(27) ring motifs, into a network consisting of rectangular layers parallel to the bc plane which are also stacked along the a-axis direction being associated through C—H⋯π (ring) interactions. The Hirshfeld surface analysis of the crystal structure indicates that the most important contributions for the crystal packing are from H⋯H (43.6%), H⋯C/C⋯H (42.0%) and H⋯O/O⋯H (8.9%) interactions.